Prior Authorization to Resort to Arbitration in Administrative Contracts: A Comparative Study between Jordanian, Egyptian and French Legislation - Almajali, Muhammad (Journal of Legal Sciences, 2026)
This research addresses the issue of “prior administrative authorization” as a condition for resorting to arbitration in administrative contract disputes. It examines this requirement as a point of delicate balance between party autonomy in contracts on the one hand, and the requirements of legality, protection of public funds, and ensuring the continuity of public service on the other. The study is based on a central question: Does this authorization constitute an objective restriction on the arbitrability of administrative contract disputes, or is it merely an internal procedural requirement governing the authority of the public official to conclude an arbitration agreement? It also examines the legal consequences of the absence of such authorization on the validity and enforceability of the arbitration agreement, both domestically and internationally. The study adopts a comparative and analytical methodology, focusing on Jordan, Egypt, and France. It examines the legal basis, nature, and limits of prior authorization, the competent authority to issue it, and its legal effects. In Egyptian legislation, prior authorization appears as an explicit requirement for concluding arbitration agreements in administrative contract disputes, linked to the approval of the competent minister or his authorized representative, while strictly limiting delegation of this power. This reflects a legislative approach aimed at regulating arbitration within the administration and reducing the risk of unjustified waiver of the jurisdiction of administrative courts. In the French legal system, the general principle is the prohibition of arbitration involving public persons, except where specific legislative provisions provide otherwise. Accordingly, authorization whether legislative or regulatory constitutes the gateway that transforms the prohibition into permissibility in limited and exceptional cases. In the Jordanian system, arbitration law generally allows public legal persons to resort to arbitration without requiring a condition equivalent to ministerial approval. This raises practical questions regarding the internal administrative controls necessary to safeguard legality and public funds when including arbitration clauses in administrative contracts.The study concludes by developing a comparative framework that distinguishes between “prior authorization” as a limitation on the authority of the administrative representative to conclude an arbitration clause, and “arbitrability of the dispute” as a matter of public order and judicial competence. It further explains the practical implications of each characterization in terms of the legal consequence of missing authorization (invalidity, non-enforceability, or liability), the scope of judicial review, and its impact on contractual stability and investment attractiveness in administrative contracts.